2022
DOI: 10.3389/fpsyg.2022.810012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the Relationship Between Emotional Intelligence and Risk Behavior: A Systematic and Meta-Analytic Review

Abstract: The aim of the present study was to carry out a qualitative and quantitative synthesis of the existing literature studying the relationship between emotional intelligence and risk behavior. We conducted a systematic review and meta-analysis of the scientific evidence available relating both constructs. Particular attention was paid to identifying possible differences in this relationship as a function of the different conceptualizations of EI and the risk domain. The study was conducted following the Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
1
4
0
2
Order By: Relevance
“…Yet, Emotional Attention was barely related to negative affective states. These findings dovetail with those of other authors who did not find significant relationships between Emotional Attention and negative experiences, such as anxiety (Guil et al, 2019), depression (Guil et al, 2022), and risky behaviors that endanger health and safety (Sánchez-López et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Yet, Emotional Attention was barely related to negative affective states. These findings dovetail with those of other authors who did not find significant relationships between Emotional Attention and negative experiences, such as anxiety (Guil et al, 2019), depression (Guil et al, 2022), and risky behaviors that endanger health and safety (Sánchez-López et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…The lack of consensus between studies could be attributable to several factors, such as the different conceptualizations of EI used (mixed model vs. ability models) or the study samples, which have been unbalanced in terms of gender and predominantly composed of young university students. Previous studies have demonstrated that gender and age have a significant impact both on levels of EI (Cabello et al, 2016(Cabello et al, , 2021Sánchez-López et al, 2022;Sánchez-Núñez et al, 2008) and the tendency to engage in risky driving behaviours (Navas et al, 2019;Oltedal and Rundmo, 2006;Ulleberg, 2001;Ventsislavova et al, 2021). In addition, driving experience is a key factor in explaining differences in driving behaviour (Di Stasi et al, 2011;Konstantopoulos et al, 2010;Megías et al, 2018).…”
Section: Emotional Intelligence and Risky Driving Behaviourmentioning
confidence: 98%
“…Higher EI scores were discovered to be associated with considerably less reactivity to stress on both a psychological and biological level 25 . A recent meta-analysis supports the existence of a correlation between EI and harmful health behaviors, such as substance abuse, risky sexual behavior, and excessive alcohol consumption 26 . Given that, do higher EI abilities help people to adopt and maintain a healthy lifestyle?…”
Section: Introductionmentioning
confidence: 94%